STRATEGI PEMASARAN USAHA BAKPIA UNTUK MENDUKUNG KEMANDIRIAN PESANTREN (STUDI KASUS : UNIT USAHA BAKPIA PONDOK PESANTREN AL MUMTAZ) - Nurlina H; Marosimy Millaty (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
Al Mumtaz Integrated Islamic Boarding School is one of the islamic boarding schools that has a pattern of thinking about economic-community science through the pesantren independence program. This is evidenced by the development of independence and business development, one of which is the Bakpia Al Mumtaz business. The purpose of this study is to provide a proposal for the right marketing strategy in the Bakpia business unit of Pondok Pesantren Al Mumtaz. The method used in this study is a qualitative approach that contains a method to collect data in written form from people and observed groups aimed at making a descriptive or systematic picture of the observed object. The analysis used is SWOT Analysis. The use of SWOT analysis is carried out to find out the internal factors of the al Mumtaz islamic boarding school business unit in developing its business, so that it can be known what are the factors of strengths and weaknesses. As for external factors to find out the opportunities and threats faced by the bakpia business of the Al Mumtaz Islamic boarding school. The results of the research analysis obtained an IFE matrix value of 3.7 and an EFE matrix value of 3.75, this shows that Bakpia Al Mumtaz's efforts are in the position of quadrant 1, which means supporting aggressive strategies. This requires Bakpia Al Mumtaz's efforts to create alternative strategies that can be used to use internal forces in seizing opportunities that exist outside of Bakpia Al Mumtaz's business.